STUDI FITOKIMIA IRVINGIA MALAYANA SEBAGAI ANTIMALARIA DARI HUTAN MERU BETIRI DALAM RANGKA DRUG DISCOVERY - Ayik Rosita Puspaningtyas (Jurnal Ilmiah Farmasi Farmasyifa, 2018)
Meru Betiri forest in Jember contains a lot of medicinal plants. Irvingia malayana (Pauh Kijang), which is one of the medicinal plants found, has been proven as an antimalarial. However, phytochemical and antimalarial studies of Irvingia malayana have never been carried out. This study was conducted for an antimalarial Drug Discovery through phytochemical study by isolating the roots, stems, and leaves of Irvingia malayana. From the analysis using FTIR, H-NMR, and GC-MS, it was concluded that the compound in the ethyl acetate extract of Irvingia malayana stem was terpenoids that was included in silymarin group as well as other plants in the genus Irvingia. The melting point of Irvingia malayana isolate was 120-121oC with white crystals. Statistical result of in vivo study showed that each group was significantly different. On day 4 after administration, IC50 showed was 11,827 mg/kgBW and day 3 was 6,927 mg/kgBW. Therefore, 3 days is the maximum duration of administration in reducing plasmodium and shows the most excellent activity as antimalarial. In in vitro study, IC50 of Irvingia malayana (62.855 ug/ml) has weak activity of antiplasmodium compared to chloroquine positive controls containing IC50 (1,114x10-3 ug/ml). Based on the data of in vivo and in vitro antimalarial activities, the compound had no antimalarial activity because the extract consisted of many components that possessed many possible synergetic mechanisms of antimalarial if compared to single compound.Keywords: